Seeking a Space of Equality: The Shifting Role of Salafi Women in Contemporary Indonesia - Ismail, Zaky; Fakhruddin, M. Anas; Bariroh, Laili; Nurhayati, Aniek (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This article aims to describe the shifting role of women in Muslim Salafist communities in Indonesia. Stereotyped as being oppressed, unrepresented, and not allowed to participate in the public sphere, the Salafi women are not expected to play an active role in their movement. Constructed on a literary study, this study finds that the female members of the Salafist movement can exercise some level of agency within the framework of structural conditions and are aware of their role. Salafist women in Indonesia are determined to play an active role in society and pursue their higher education, thus preparing them to serve as agents in the movement’s da‘wah activities. Although the women’s role is confined to activities within their community, they help recruit new female members and maintain the movement’s social networks.